Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A=(-2;2)
B=[-3;2)
A giao B=(-2;2)
A\B=\(\varnothing\)
B\A=[-3;-2]
\(C_R\left(A\cap B\right)=R\backslash\left(-2;2\right)=(-\infty;-2]\cup[2;+\infty)\)
a: A=(-7/4; -1/2]
\(B=\left(-\dfrac{9}{2};-4\right)\cup\left(4;\dfrac{9}{2}\right)\)
\(C=\left(\dfrac{2}{3};+\infty\right)\)
b: \(\left(A\cap B\right)\cap C=\varnothing\)
\(\left(A\cup C\right)\cap\left(B\A\right)\)
\(=(-\dfrac{7}{4};-\dfrac{1}{2}]\cup\left(\dfrac{2}{3};+\infty\right)\cap\left[\left(-\dfrac{9}{2};-4\right)\cup\left(4;\dfrac{9}{2}\right)\right]\)
\(=\left(4;\dfrac{9}{2}\right)\)
Bài 3:
a: \(\left(-\infty;\dfrac{1}{3}\right)\cap\left(\dfrac{1}{4};+\infty\right)=\left(\dfrac{1}{4};\dfrac{1}{3}\right)\)
b: \(\left(-\dfrac{11}{2};7\right)\cup\left(-2;\dfrac{27}{2}\right)=\left(-\dfrac{11}{2};\dfrac{27}{2}\right)\)
c: \(\left(0;12\right)\text{\[}5;+\infty)=\left(0;5\right)\)
d: \(R\[ -1;1)=\left(-\infty;-1\right)\cup[1;+\infty)\)
\(B=\left\{-3;-2;-1;0;1;2;3;4\right\}\)
Để \(B\cap C=\varnothing\Leftrightarrow a\in D\)
Với \(D=\left\{x\in Z;x\le-4\right\}\)
1: A={-3;-2;-1;0;1;2;3}
B={2;-2;4;-4}
A giao B={2;-2}
A hợp B={-3;-2;-1;0;1;2;3;4;-4}
2: x thuộc A giao B
=>\(x=\left\{2;-2\right\}\)
Lời giải:
Theo đề thì: \(B\subset A\) nên \(A\cap B = B [-2;1)\)